Vulnerability of the region to socio-economic drought (ESCWA water development report, 2005)
Of all natural hazards, drought affects the greatest number of people globally, with devastating impact. The vulnerability of communities to drought is dependent on a host of physical, social, environmental and economic characteristics. In recent years, owing to population growth, soil degradation, increased desertification, and projected climate change scenarios, drought research and planning has become crucial to averting and mitigating drought disasters. Drought vulnerability research examines how the impacts of drought are a result of the interactions of social, political and economic systems, as well as the meteorological drought phenomenon. However, in the past, drought monitoring and research focused almost exclusively on the relation of climatic patterns and rainfall deficiencies to water supply. However, such a focus does not examine how human water use exacerbates deficits in water supply and quality. As a result, there is a worldwide insufficiency of disaster preparedness and mitigation methods that adequately address the socio-economic effects of drought and integrate drought planning into water resource management. The objective of the present study is to address the gap in understanding socio-economic drought in the Economic and Social Commission for Western Asia (ESCWA) region, and to raise awareness of the importance of developing drought detection, prevention, preparedness and mitigation measures regionally. In order to examine the socio-economic impacts of drought, this report presents measures taken on drought management and mitigation from three regional case-studies--Jordan, the Syrian Arab Republic and Yemen--and addresses the need for regional drought preparedness planning.